Activity of antioxidant enzymes and malondialdehyde content in sweet cherry fruits under living mulch conditions - Герасько, Тетяна Володимирівна; Колесніков, Максим Олександрович; Нєжнова, Ніна Геннадіївна; Нінова, Галина Василівна; Алексєєва, Ольга Миколаївна; Herasko, Tetiana; Kolesnikov, Maksym; Nezhnova, Nina; Ninova, Halyna; Alekseeva, Olha; Kovtuniuk, Zoia (Литва : 2023, 2023)
EN: Living mulch is the most natural soil cover in the orchard; however, competition with grasses creates stressful conditions for fruit crops. The reaction of plants to stress can be determined by the activity of antioxidant enzymes and the content of lipid peroxidation products in plant tissues. The reaction of trees to coexistence with living mulch (natural grasses that were mowed four times during the growing season) was studied in an organic sweet cherry (Prunus avium L.) orchard with chestnut, sandy soil in the warm and arid conditions of Southern Steppe of Ukraine. The aim of the research was to determine how the living mulch (compared to bare fallow) affects the activity of antioxidant enzymes and the content of malondialdehyde (MDA) in sweet cherry fruits at different stages of fruit development. It was determined that living mulch significantly increased the activity of ascorbate peroxidase (by 21–52%), polyphenol oxidase (by 22–42%), and peroxidase (26–34%) in the tissues of sweet cherry fruits. The MDA content was significantly higher in sweet cherry fruits produced under living mulch (compared to the fruits of a bare fallow management system) only at the stage of partial reddening in 2018 (by 41%) and at the stage of stone hardening in 2019 (by 58%). At the picking maturity stage, no significant difference between the treatments of the experiment was found, which indicates the successful overcoming of oxidative stress caused by competition with natural grasses.
Keywords: Prunus avium; catalase; ascorbate peroxidase; polyphenol oxidase; peroxidase